NUC-1031/cisplatin versus gemcitabine/cisplatin in untreated locally advanced/metastatic biliary tract cancer (NuTide: 121) - McNamara, Mairéad Geraldine; Goyal, Lipika; Doherty, Mark; Springfeld, Christoph; Cosgrove, David; Sjoquist, Katrin Marie; Park, Joon Oh; Verdaguer, Helena; Braconi, Chiara; Ross, Paul J; Gramont, Aimery De; Zalcberg, John Raymond; et al. (Future oncology, 2020)
Gemcitabine/cisplatin is standard of care for first-line treatment of patients with advanced biliary tract cancer (aBTC); new treatments are needed. NUC-1031 is designed to overcome key cancer resistance mechanisms associated with gemcitabine. The tolerability/efficacy signal of NUC-1031/cisplatin in the Phase Ib ABC-08 study suggested that this combination may represent a more efficacious therapy than gemcitabine/cisplatin for patients with aBTC, leading to initiation of the global NuTide:121 study which will include 828 patients ≥18 years with untreated histologically/cytologically-confirmed aBTC (including cholangiocarcinoma, gallbladder or ampullary cancer); randomized (1:1) to NUC-1031 (725 mg/m2)/cisplatin (25 mg/m2) or gemcitabine (1000 mg/m2)/cisplatin (25 mg/m2), on days 1/8, Q21-days. Primary objectives are overall survival and objective response rate. Secondary objectives: progression-free survival, safety, pharmacokinetics, patient-reported quality of life and correlative studies.(Investigational new drug (IND) number: 139058, European Clinical Trials database: EudraCT Number 2019-001025-28, ClinicalTrials.gov identifier: NCT04163900).
Gesehen am 29.09.2020